2018
DOI: 10.7554/elife.32346
|View full text |Cite
|
Sign up to set email alerts
|

Myotubularin related protein-2 and its phospholipid substrate PIP2 control Piezo2-mediated mechanotransduction in peripheral sensory neurons

Abstract: Piezo2 ion channels are critical determinants of the sense of light touch in vertebrates. Yet, their regulation is only incompletely understood. We recently identified myotubularin related protein-2 (Mtmr2), a phosphoinositide (PI) phosphatase, in the native Piezo2 interactome of murine dorsal root ganglia (DRG). Here, we demonstrate that Mtmr2 attenuates Piezo2-mediated rapidly adapting mechanically activated (RA-MA) currents. Interestingly, heterologous Piezo1 and other known MA current subtypes in DRG appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 88 publications
1
38
0
Order By: Relevance
“…There are several lines of evidence, suggesting that PIEZO2 interacts with cellular components to fulfill its physiological role. For instance, PIEZO2's association with stomatin-like protein 3 and cholesterol increases its sensitivity to mechanical stimuli 18,19 , sensitization by inflammatory agents via the bradykinin receptor 7 , potentiation by Gi-coupled receptor activation 20 , and regulation by phosphoinositide lipids 21,22 . Moreover, it has been suggested that PIEZO2 requires cytoskeletal elements such as actin and tubulin for normal function 8 .…”
mentioning
confidence: 99%
“…There are several lines of evidence, suggesting that PIEZO2 interacts with cellular components to fulfill its physiological role. For instance, PIEZO2's association with stomatin-like protein 3 and cholesterol increases its sensitivity to mechanical stimuli 18,19 , sensitization by inflammatory agents via the bradykinin receptor 7 , potentiation by Gi-coupled receptor activation 20 , and regulation by phosphoinositide lipids 21,22 . Moreover, it has been suggested that PIEZO2 requires cytoskeletal elements such as actin and tubulin for normal function 8 .…”
mentioning
confidence: 99%
“…It was reported that PI(3,5)P2, a product of PI3K positively regulates Piezo2 channels (Narayanan et al, 2018). Due to lack of reliable specific probes for PI(3,5)P2 (Hammond et al, 2015) the involvement of this lipid in Piezo2 potentiation by Gicoupled receptors is difficult to test, and wortmannin was reported to have only marginal effect on Piezo2 activity evoked by the knockdown of the myotubularin related protein-2 (Mtmr2), a phosphatase enzyme that dephosphorylates PI(3,5)P2 (Narayanan et al, 2018). Further experimentation and biochemical tools are needed to conclusively determine the mechanism of the involvement of PI3K and MAPK in regulating Piezo2 activity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we tested if activation of GABAB receptors could influence the activity of Piezo2 channels. We mechanically stimulated, with a glass probe, large diameter DRG neurons (cell capacitance >40 pF), which are most likely mechanoreceptors (Narayanan et al, 2018), and recorded rapidly adapting-mechanically activated (RA-MA) currents, attributed to Piezo2 channels (Coste et al, 2010;Woo et al, 2015). First, we repetitively applied short mechanical stimulations of the same amplitude every 30 seconds, and after 3 minutes of recording mechanically activated currents, we activated GABAB receptors by treating the cells with 25 µM baclofen.…”
Section: Gabab Receptor Activation Potentiates Piezo2-like Currents Imentioning
confidence: 99%
“…However, the precise mechanisms through which diseases and/or injuries alter the mechanical sensitivity of ion channels leading to the perception of pain instead of touch are unknown. It may involve various pathways such as(1) PKA and PKC signaling that lead to sensitization of ion channels (Brackley et al, 2017; Dubin et al, 2012; Fan et al, 2009; Fischer et al, 2010; Meents et al, 2017; Schmidt et al, 2009); (2) alterations in the composition of the plasma membrane lipid bilayer, and subsequent alterations in gating of a mechanically-gated ion channel (Barabas et al, 2014; Narayanan et al, 2018); or (3) novel channel interactions such as the coupling of an ion channel normally not involved in mechanosensation to a mechanically gated ion channel or the coupling of a mechanically sensitive ion channel to an accessory protein that enhances its function (e.g., TMEM150C) (Anderson et al, 2018; Dubin et al, 2017). Ultimately, more research is needed to determine how mechanically gated ion channels become sensitized in pathological states associated with painful touch.…”
Section: Introductionmentioning
confidence: 99%